Analysis of clinical features and lifestyle in Korean senile gluteal dermatosis patients. (31st July 2015) - Moon, Sung Hyuk; Kang, Boo Kyoung; Jeong, Ki Heon; Shin, Min Kyung; Lee, Mu‐Hyoung
Abstract: Background: Senile gluteal dermatosis (SGD) is characterized by hyperkeratotic lichenified skin lesions on the superior part and both sides of the anal cleft. These lesions are particularly prevalent in sedentary and elderly patients. Objectives: The purpose of this study was to investigate the prevalence, clinical manifestations, and other clinical characteristics of SGD in elderly Korean individuals. Methods: A total of 280 subjects aged >60 years identified through the outpatient department at our hospital were included in this study. Basic clinical information was collected, and the subjects were evaluated clinically for gluteal lesions. Skin biopsies were performed in eight of the patients diagnosed with SGD. Results: Among a total of 280 subjects, 37 were diagnosed with SGD. Their mean age was 70.4 years. The prevalence of SGD was found to increase with age. In addition, there was a significant positive correlation between SGD and lower lean body mass, longer period of a sedentary lifestyle, use of a Korean‐style mattress, and diabetes mellitus. Most patients had either mild symptoms or were asymptomatic. Skin biopsies showed hyperkeratosis, acanthosis, follicular plugging, and meandering superficial vessel proliferation with mild lymphohistiocytic infiltration. None of the biopsy specimens exhibited amyloid deposition. Conclusions: Our findings suggest that SGD is a common disorder in elderly Korean individuals and is associated with prolonged periods of rest such as those occurring in a highly sedentary lifestyle and with sleeping on a Korean‐style mattress.